Terminal glycosylation pattern as a determinant of human iPSC-derived cardiomyocytes transduction with AAV vectors. (10th June 2022) - Kraszewska, I; Andrysiak, K; Sarad, K; Dulak, J; Jazwa-Kusior, A
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Faculty of Biochemistry, Biophysics and Biotechnology, Jagiellonian University, Young scientists grant MNS9/2021 Polish National Science Centre PRELUDIUM grant 2019/33/N/NZ1/03066 Introduction: Although gene therapy has become a feasible alternative to regular treatment in numerous disorders, efficient targeting of human heart still seems out of reach. So far, adeno-associated viral vectors (AAVs) have been the most promising transgene carriers in in vivo applications. Transduction with AAVs relies on serotype-specific binding to the glycan residues on the cell surface. While AAV serotype 9 (AAV9) - binding galactose - was successfully used for delivery of therapeutic genes to cardiac muscle in murine models, its effect was underwhelming in large animals. Switching the serotype to AAV1 or AAV6 – binding sialic acids – enabled transduction of porcine hearts, and cardiomyocytes derived from human induced pluripotent stem cells (hiPSC) in 2D in vitro culture. But, as evidenced in clinical trials where less than 1% of heart cells contained delivered transgene, such strategy was not suitable for in vivo application in humans. Purpose: Taking into account differences in glycosylation patterns between humans and other mammals, we aimed to investigate the role of surface glycans in AAV6 and AAV9 transduction mechanism in 2D and 3D cultures of human cardiomyocytes. Methods: We generated hiPSC- derived cardiomyocytes (hiPSC-CMs) and epicardial fibroblasts (hiPSC-CFs). Cells were cultured in regular 2D conditions or 3D co-cultures (as spheroids), since direct cells interaction may influence the availability of terminal sugar residues. Surface glycans were stained with lectins and imaged using confocal microscope. Results: While in 2D conditions AAV6 transduces hiPSC-CMs very efficiently, it is significantly less potent in 3D culture. Conversely, AAV9 maintains most of its functionality in 3D model. Our data collected from spheroids, indicate that cells in such 3D cultures undergo significant changes in terminal glycosylation pattern. While the level of galactose (AAV9 receptor) increased from day 1 to day 7, the signal from sialic acids attached to galactose (AAV6 receptor) decreased. This effect was accompanied by the upregulation of sialidase-3 expression, that regulates availability of galactose residues on the cell surface. As a result, transduction efficiency was improved in spheroids exposed to AAV9 on day 7 of 3D culture, in comparison to those transduced on day 1. Inhibition of sialidases activity with NADNA reduced the level of terminal galactose in both, hiPSC-CMs and hiPSC-CFs, and was associated with more efficient transduction of cardiomyocytes with AAV6, and less efficient transduction with AAV9. Additionally, we observed that galactosylation of collagen can be another factor that influences cell-vector interaction in 2D and 3D culture. Conclusions: Our results demonstrate that the availability of terminal sugar residues is a key factor regulating transduction of hiPSC-CMs with AAV vectors, and underline the need for development of appropriate models for testing of AAV functionality in preclinical studies.